From fiber curls to mesh waves: a platform for the fabrication of hierarchically structured nanofibers mimicking natural tissue formation. Issue 30 (19th July 2019) - Chen, Honglin; Baptista, Danielle F.; Criscenti, Giuseppe; Crispim, João; Fernandes, Hugo; van Blitterswijk, Clemens; Truckenmüller, Roman; Moroni, Lorenzo
Abstract : Bioinstructive scaffolds for regenerative medicine are characterized by their intrinsic properties that are capable of directing cell response and promoting wound healing. Abstract : Bioinstructive scaffolds for regenerative medicine are characterized by intrinsic properties capable of directing cell response and promoting wound healing. The design of such scaffolds requires the incorporation of well-defined physical properties that mimic the native extracellular matrix (ECM). Here, inspired by epithelial tissue morphogenesis, we present a novel approach to code nanofiber materials with controlled hierarchical wavy structures resembling the configurations of native EMC fibers through using thermally shrinking materials as substrates onto which the fibers are deposited. This approach could serve as a platform for fabricating functional scaffolds mimicking various tissues such as trachea, iris, artery wall and ciliary body. Modeling affirms that the mechanical properties of the fabricated wavy fibers could be regulated through varying their wavy patterns. The nanofibrous scaffolds coded with wavy patterns show an enhanced cellular infiltration. In addition, we further investigated whether the wavy patterns could regulate transforming growth factor-beta (TGF-β) production, a key signalling pathway involved in connective tissue development. Our results demonstrated that nanofibrous scaffolds coded with wavy patterns could induce TGF-β expression without the addition of a soluble growth factor. Our new approach could open up new avenues for fabricating bioinstructive scaffolds for regenerative medicine.